Različno razumevanje in pomen biodiverzitete v ekologiji, posebno v fitocenologiji - Robič, Dušan (Zbornik gozdarstva in lesarstva, 2000)
The review paper gives terminological, conceptual and applicable aspects of biodiversity. Based on relevant literature the author has found that frequencyof use of biodiversity tools depends on the nature of the research object, goals of investigation and the researcher?s intention as well. The increase of interest in biodiversity tools is significant. Species diversity can be an important part of structural analyses of forest communities. It correlates with other elements of forest ecosystem; therefore it can be a useful and efficient tool to determine and to explain phenomena concerning forest ecosystems and their functions.
Keywords: biodiversity; biodiverziteta; biotska raznovrstnost; ecology; ekologija; fitocenologija; phytosociology